Oncogenes and Clotting Factors: The Emerging Role of Tumor Cell Genome and Epigenome in Cancer-Associated Thrombosis - Tawil, Nadim; Bassawon, Rayhaan; Rak, Janusz (Seminars in Thrombosis and Hemostasis, 2019)
There are emerging linkages between biological and genetic aspects of cancer progression and the mechanisms of cancer-associated thrombosis. It is argued that reciprocal influences between cancer cells, their associated vascular stroma, and the hemostatic system may shape the mechanism of coagulopathy. In this regard, glioblastoma multiforme offers a paradigm where the prevalent occurrence of local microthrombosis and peripheral venous thromboembolism can be linked to the profiles of oncogenic driver mutations and their impact on the expression of coagulation-related genes (coagulome). These relationships can be recapitulated in cellular models of glioblastoma, where the expression of tissue factor, podoplanin, and the release of procoagulant microparticles (extracellular vesicles) remains under the control of oncogenic pathways (epidermal growth factor receptor variant III, isocitrate dehydrogenase 1). These pathways define molecular subtypes of glioblastoma that express differential coagulomes. Moreover, single-cell sequencing of glioblastoma samples reveals a combinatorial rather than common profile of both subtype markers and coagulation-related genes. Based on these emerging observations, the authors suggest that cancers may operate as coagulant composites, where individual cells and their dominant populations express different procoagulant phenotypes, resulting in the net impact on the hemostatic system. They suggest that relating these mechanisms to clinical presentations of thrombosis may facilitate a more causality-based, personalized, and possibly cancer-specific thromboprophylaxis and treatment.
Keywords: coagulome; oncogenes; glioblastoma; molecular classification; single-cell sequencing